2022
DOI: 10.3389/fmicb.2022.994151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose oxidase on growth performance, clinical symptoms, serum parameters, and intestinal health in piglets challenged by enterotoxigenic Escherichia coli

Abstract: Glucose oxidase (GOD) could benefit intestinal health and growth performance in animals. However, it is unknown whether GOD can protect piglets against bacterial challenge. This study aimed to evaluate the protective effects of GOD on growth performance, clinical symptoms, serum parameters, and intestinal health in piglets challenged by enterotoxigenic Escherichia coli (ETEC). A total of 44 male weaned piglets around 38 days old were divided into four groups (11 replicates/group): negative control (NC), positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Glucose oxidase (GOD) is an aerobic dehydrogenase that originates from the fermentation of specific fungal strains, including Aspergillus and Penicillium (12). This enzyme is capable of oxidizing β-D-glucose into gluconic acid, while also producing hydrogen peroxide (HP) through the consumption of oxygen (13). HP can inhibit the growth of harmful gut bacteria and prevent bacterial invasion (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose oxidase (GOD) is an aerobic dehydrogenase that originates from the fermentation of specific fungal strains, including Aspergillus and Penicillium (12). This enzyme is capable of oxidizing β-D-glucose into gluconic acid, while also producing hydrogen peroxide (HP) through the consumption of oxygen (13). HP can inhibit the growth of harmful gut bacteria and prevent bacterial invasion (14).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dietary supplementation of 3,000 U/kg GOD can increase the total superoxide dismutase (T-SOD) and glutathione peroxidase (GSH-Px) activity in the jejunum of piglets (19). Research shown that 200 mg/kg glucose oxidase reduced the ETEC induced decrease of IgG content and the abundance of Lactobacillaceae and Lactobacillus salivarius in the intestine (13).…”
Section: Introductionmentioning
confidence: 99%